Characterization of nivolumab-associated skin reactions in patients with metastatic non-small cell lung cancer. (1st November 2016) - Hasan Ali, Omar; Diem, Stefan; Markert, Eva; Jochum, Wolfram; Kerl, Katrin; French, Lars E.; Speiser, Daniel E.; Früh, Martin; Flatz, Lukas
ABSTRACT: Immune checkpoint inhibitors have led to considerable therapy improvement in cancer patients. Autoimmune side effects including skin reactions are frequently observed. In melanoma, those include rash and vitiligo and were shown to be associated with a prolonged overall survival. Little is known about skin reactions in non-small cell lung cancer (NSCLC) patients during immunotherapy. Here, we retrospectively investigated immune-related adverse skin reactions (irAEs) in 40 patients with metastatic NSCLC treated with the anti-PD-1 antibody nivolumab. 7 out of 40 patients (17%) developed an irAEs. Skin irAEs correlated with tumor responses in 5 of 12 responders (42%) as compared to 2 of 27 non-responders (7%). Histologically, scaly plaques showed dermatitis consisting mainly of lymphocytes. We observed a positive correlation between skin irAEs and tumor responses in patients with NSCLC treated with nivolumab. Patterns of lymphocytic skin infiltration differed depending on the histological tumor subtype (adenocarcinoma versus squamous cell carcinoma NSCLC).